The role of the injection Botulinum Toxin A in cases of Essential Blepharospasm Syndrome, Hemifacial Spasm and Meige’s Syndrome - Bastola, P; Chaudhary, M; Agrawal, J P; Shah, D N (Kathmandu University Medical Journal, 2012)
Background Benign Essential Blepharospasm Symdrome is a neuropathologic disorder. The cause of blepharospasm is multifactorial. It is unlikely that a single defect in this elusive control centre is the primary cause of this disease. Objectives To evaluate the role of botulinum toxin A in treating cases of Essential Blepharospasm Symdrome, Hemifacial Spasm and Meige’s Syndrome, and to assess orbicularis oculi muscle post treatment, in the patients who attended neuro-ophthalmology clinic and the general outpatient department of BP Koirala Lions Centre for Ophthalmic studies. Methods A prospective, interventional study was carried out on all the patients of Essential Blepharospasm Symdrome, Hemifacial Spasm and Meige’s syndrome who underwent treatment with botulinum toxin A in BP Koirala Lions Centre for Ophthalmic studies during a study period of one and half years. Pre- treatment grading of the spasm was done with Jankovic spasm grading and post treatment response was seen with assessment of orbicularis oculi muscle and improvement in functional impairment scale. Relevant findings were noted. Results A total of 40 cases were enrolled in the study. The mean Jankovic spasm grading in cases of essential blepharospasm, hemifacial spasm and Meige’s syndrome was 3.61 (±Standard deviation 0.50, range 3-4), 3.21 (±Standard deviation 0.63, range 2-4) and 3.67 (+- Standard deviation 0.57, range 3-4) respectively. The mean value for reappearance of significant spasms (in months) in cases of essential blepharospasm, hemifacial spasm and Meige’s syndrome was 4.3 (± Standard deviation 1.6, range 2.0-6.5), 5.8 (±Standard deviation 1.4, range 3-8) and 4.5 (± Std.deviation 2.8, range 2.5-6.5) respectively. Blepharoptosis was the commonest complication accounting for 66.6% of the complications. Conclusions The movement disorders like Essential Blepharospasm, Hemifacial Hpasm and Meige’s syndrome are treated by different modalities. An acceptable and effective treatment modality has been a long felt need in these cases. Our study has shown that injection of botulinum toxin A has been a safe and effective method of treating these cases in Nepal. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6217 Kathmandu Univ Med J 2010;8(3):305-10